Supply Chain Optimization of Bojonegoro Agro-Logistics Hub Through HACCP-Based Hygienic Architectural Design Implementation - Bayu Dwi Saputra; Joko Santoso (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This research addresses the design of an Agro-Logistics Hub in Bojonegoro as a strategic solution to agricultural supply chain inefficiencies, price fluctuations, and post-harvest losses resulting from inadequate cold chain facilities. The primary objective of this design is to establish a centralized distribution node and a regional price stabilizer in alignment with the Bojonegoro Regional Medium-Term Development Plan (RPJMD). This study employs a qualitative methodology, utilizing Multi-Criteria Analysis (MCA) for site selection and comparative studies between PIKJ and Puspa Agro. The architectural approach integrates logistics through cross-docking circulation and Hygienic Architecture based on HACCP standards, ensuring strict zoning and the utilization of food-grade materials. The resulting design features modular facilities equipped with large-scale cold storage, sorting areas, and farmer education centers. The selected site on Jalan Ngambon Ngasem (score: 2.8) was proven to be more efficient in streamlining distribution channels compared to urban alternatives. Furthermore, energy mitigation strategies are implemented through extensive rooftop solar power systems (PLTS) to guarantee power stability for the cold storage units. Ultimately, this infrastructure is envisioned as a key driver for food security and sustainable economic growth in Bojonegoro.